Bioprinted hydrogels in bone regeneration: a bibliometric analysis - Zhang, Huijie; Li, Xiaoyu; Jia, Zhenyu; Jiao, Kun; Liu, Chen; Deng, Zixiang; Bai, Yushu; Wei, Xianzhao; Zhou, Xiaoyi (Frontiers in Pharmacology, 2025)
BackgroundThe application of bioprinted hydrogels in the field of bone regeneration is garnering increasing attention. The objective of this study is to provide a comprehensive overview of the current research status, hotspots and research directions in this field through bibliometric methods, and to predict the development trend of this field.MethodsA search was conducted on 27 December 2024, for papers published on the Web of Science from 2010 to 2025. We used the bibliometrix package in the software program R to analyze the retrieved data and VOSviewer and CiteSpace to visualize hotspots and research trends in bioprinted hydrogels for bone regeneration.ResultsWe identified and reviewed 684 articles published in this field between 2010 and 2025. A total of 811 institutions and 1,166 researchers from 41 countries/regions contributed to these publications. Among them, China led in terms of the number of articles published, single-country publications (SCP), and multi-country publications (MCP). Our bibliometric-based visualization analysis revealed that the mechanical properties and osteogenic differentiation capacity of biomaterials have been a focal research topic over the past decade, while emerging research has also concentrated on the in vitro fabrication of stem cells for bone regeneration and osteogenic differentiation, particularly the precise application of in situ stem cell-loaded bioprinted organoids.ConclusionThis study provides an in-depth analysis of the research trajectory in the application of bioprinted hydrogels for bone regeneration. The number of research papers in this field is increasing annually, and the main research hotspots include bone regeneration, 3D printing, scaffolds, and hydrogels. Future research directions may focus on gelatin, additive manufacturing, and growth factors. Additionally, international collaboration is essential to enhance the effectiveness of bioprinted hydrogels in bone regeneration applications.